2017
DOI: 10.1136/oemed-2017-104391
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to glycol ethers and cryptorchidism and hypospadias: a nested case–control study

Abstract: In view of the toxicological plausibility of our results, this study, despite its small sample size, raises concern about the potential developmental toxicity of MAA on the male genital system and calls for thorough identification of current sources of exposure to MAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…in 2013 dealt with glycol ethers, including phenoxyethanol (Table ). More recently, the same team also recently published two other observational studies on glycol ethers, including phenoxyethanol …”
Section: Review Of Safety Datamentioning
confidence: 99%
See 3 more Smart Citations
“…in 2013 dealt with glycol ethers, including phenoxyethanol (Table ). More recently, the same team also recently published two other observational studies on glycol ethers, including phenoxyethanol …”
Section: Review Of Safety Datamentioning
confidence: 99%
“…The third study was a case–control study nested in the two joint PELAGIE and EDEN cohorts. Its results showed that there was no association between urinary concentrations of phenoxyacetic acid and cryptorchidism or hypospadias …”
Section: Review Of Safety Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The recent publication by Warembourg et al 1 suggests several associations between exposure to glycol ethers during pregnancy and the development of male genital anomalies. We consider that a number of the findings and assumptions are of dubious credibility and, while some reach statistical significance, it is doubtful that a link with glycol ether exposure is biologically credible.…”
mentioning
confidence: 99%